U.S.-China trade war 2.0: What are the implications for global oilseed markets? - Glauber, Joseph W.; Gianatiempo, Juan Pablo; Piñeiro, Valeria (International Food Policy Research Institute, 2025)
The U.S. government’s most recent tariff measures are strongly focused on China, in what looks to be a replay of the 2018-2019 U.S.-China trade war that resulted in large losses for both countries. That conflict significantly diverted agricultural trade, as China sought other suppliers and the U.S. attempted to find new markets for its products. Each country’s current tariffs targeting the other now far exceed the highest levels of that previous trade war. Depending on their duration, these measures could have serious impacts on the economies of the United States, China, and the global trading system as a whole.